(untitled) (Journal of Partial Differential Equations, 2022)
This paper is concerned with the existence of pullback attractors for three dimensional generalized Navier-Stokes equations with delay. According to compact argument, the existence and uniqueness of weak solutions are proved by using Galerkin method, and the continuous dependence of solutions on initial values is also shown. Based on the asymptotic compactness via weak convergence method and pullback absorbing set on appropriate functional phase spaces, we get the existence of pullback attractors.